1991
DOI: 10.1590/s0036-46651991000100015
|View full text |Cite
|
Sign up to set email alerts
|

Diagnosis of Helicobacter pylori: comparison of an urease test, histological visualization of curved bacteria and culture

Abstract: Helicobacter pylori was investigated in 189 patients for culture, microscopic visualization of campylobacter-like organisms (CLO) and a ten minute urease test. In 136 (72%) the bacteria was isolated, and in 98 of them CLO were histologically detected. Specificity, sensitivity, positive and negative predictive values of microscopic visualization of CLO were: 0.77, 0.73, 0.97 and 0.51, respectively; 98 culture-positive patients were urease test positive. Specificity, sensitivity, positive and negative predictive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

1992
1992
2017
2017

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 10 publications
0
4
0
Order By: Relevance
“…H. pylori infection has been associated with gastric injury and an increased risk of carcinoma (1,3,22). Two earlier studies in Costa Rica reported isolation of H. pylori in 62 out of 92 (67%) and 136 out of 189 (72%) adult dyspeptic patients respectively (8,9). However, these prevalence values relate to dyspeptic patients, and no information is available regarding the general population.…”
Section: Discussionmentioning
confidence: 99%
“…H. pylori infection has been associated with gastric injury and an increased risk of carcinoma (1,3,22). Two earlier studies in Costa Rica reported isolation of H. pylori in 62 out of 92 (67%) and 136 out of 189 (72%) adult dyspeptic patients respectively (8,9). However, these prevalence values relate to dyspeptic patients, and no information is available regarding the general population.…”
Section: Discussionmentioning
confidence: 99%
“…One day after the final administration, the mice were killed and their gastric mucosa was biopsied for the detection of H. pylori . The presence of H. pylori in gastric mucosa was confirmed by direct bacterial culture, as previously described ( 25 ). For culturing, tissue was rubbed across the surface of a plate containing a selective medium of 10% bovine serum, 6 μg/mL vancomycin, 5 μg/mL trimethroprim, 10 μg/mL polymyxin B, 200 μg/mL bacitracin, 8 μg/mL amphotericin B, and 10 μg/mL nalidixic acid.…”
Section: Methodsmentioning
confidence: 99%
“…The presence of H. pylori in gastric mucosa was confirmed by direct bacterial culture, as described previously (25). For culturing, the tissue was rubbed across the surface of a plate with selective medium containing 10% bovine serum, 6 μg/mL vancomycin, 5 μg/mL tri-methroprim, 10 μg/mL polymyxin B, 200 μg/mL baci-tracin, 8 μg/mL amphotericin B and 10 μg/mL nalidixic acid.…”
Section: Methodsmentioning
confidence: 99%